Analisis Faktor Internal dan Eksternal yang Mempengaruhi Siswa dalam Mengikuti Pembelajaran Olahraga Bola Voli Kelas VIII SMP Negeri 10 Kota Jambi - Sari, Irma Maya; Widowati, Atri; Muzaffar, Ahmad (MAN Insan Cendekia Jambi, 2025)
This study aims to determine the internal and external factors that influence students in participating in volleyball game learning for class VIII students at SMP Negeri 10 Jambi City. The research method used descriptive quantitative with a survey approach to 50 randomly selected eighth grade students. Internal factors were measured through interest and Body Mass Index (BMI), while external factors were measured through the role of teachers and infrastructure. The results showed internal factors (interest) in the fairly appropriate category 44%, external factors (teacher) in the appropriate category 52%, and the combination of internal-external in the appropriate category 62%. For BMI, 54% of students were in the thin category, 40% normal, and 6% fat. Volleyball facilities are available but volleyball ball conditions are insufficient with 5 in good condition and 2 damaged. The conclusion shows that external factors (teachers) are more influential than internal factors (interest) in volleyball learning, while the physical condition of students is mostly in the thin category which can affect performance in sports.